Painted Poetry, Poetry by the Meter. The Visual Vanguard in Poémes Peintre (1922) by Vicente Huidobro and 5 Meters of Poems (1927) by Carlos Oquendo de Amat - Ayram, Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this article, examines the exhibition and construction of some of the Painted Poems that Vicente Huidobro exhibited in Paris, in 1922, a fact that marks the provocative relationship between poetry and painting throughout his art exhibition. On the other hand, the production of poetry is explored as a dynamic and mobile aesthetic object in 5 metros de poemas by Carlos Oquendo de Amat. With the analysis of this poetic production I propose to establish a comparison between the poems "Paisaje" by Huidobro,  and "Film del paisaje" by Oquendo de Amat, to point out how the need for design and the graphic-spatial dimension of the poems marked the avant-garde spirit in Latin America, while at the same time leading the poets to conceive poetry as a material and aesthetic production beyond the traditional support and format of the book.